"مساهمة الاستدامة المالية في تحقيق أهداف التنمية المستدامة في الجزائر .2020- دراسة تطبيقية للفترة: 2000" - عبد الغني, بن موسى; عبد العالي, قادي (University of eloued جامعة الوادي, 2020)
"إن تحقيق التنمية الاقتصادية هو هدف تسعى إليه معظم المجتمعات ، متمثلة في أنماطها المختلفة من الدول والكتل الإقليمية. مع صدور القانون العضوي رقم 15-18 في عام 2018 المتعلق بالقوانين المالية ، والتي من خلالها تهدف السلطات في الجزائر إلى رفع كفاءة المالية العامة وتحقيق الاستدامة المالية ، والتأثير الإيجابي لذلك على فعالية أدواتهم علىمكونات الاقتصاد الكلي وبالتالي تساهم في تحقيق التنمية المستدامة في الجزائر.هدفت الدراسة إلى الإجابة عن السؤال التالي: ما مدى مساهمة السلامة المالية في تحقيقها التنمية المستدامة في الجزائر؟. اعتمادا على النهج الوصفي في إطار التعرف على مفاهيم عامة عن موضوع الدراسة وتوظيف ثبات السلاسل الزمنية طرق تحديد مدى استقرار متغيرات الاستدامة المالية في الجزائر. وأكدت النتائج قدرة الجزائر على تنويع وتحفيز الإيرادات الحكومية لتنمو بمعدل أسرع من الإنفاق الحكومي مما يؤدي إلى سداد العجز واحتواءه من أعباء الديون ، من أجل تحقيق شرط الاستدامة المالية ""ABSTRACT Achieving economic development is a goal pursued by most societies, represented in their various kines of states and regional blocs. With the issuance of Organic Law No. 15-18 in the year 2018 related to the financial laws, through which the authorities in Algeria aim to raise the efficiency of public finances and achieve financial sustainability, and the positive impact this has on the effectiveness of their tools on the components of the macro economy and thus contribute to achieving sustainable development in Algeria. The study aimed to answer the following question, What is the contribution of financial safety to achieving sustainable development in Algeria ?. depending on the descriptive approach within the framework of exposure to general concepts about the subject of the study, and the employment of time-series stability methods to determine the extent of the stability of financial sustainability variables in Algeria. The results confirmed Algeria's ability to diversify and stimulate its government revenues so that they grow at a faster rate than government expenditures, which leads to the payment of the deficit and the containment of debt burdens, in order to achieve the condition of financial sustainability"
مذكرة ماستر اقتصاد وتسيير مؤسسات
Keywords: الاستدامة المالية، التنمية المستدامة،السلامة المالية; Viabilité financière, développement durable, solidité financière